Selective recruitment of lymphocyte subsets to the inflamed appendix. - Soo, K; Michie, C; Baker, SR; Wyllie, J; Beverley, P (1995)
Total lymphocyte counts and the distribution of lymphocyte subsets were determined in peripheral venous blood and appendiceal mononuclear cells from 60 patients who underwent appendicectomy for the clinical diagnosis of appendicitis. A significant peripheral lymphopenia was observed in the 46 patients with histologically confirmed acute appendicitis which was accompanied by an increase in the appendiceal lymphocyte concentration. There was an even greater depletion of CD45RO+ (memory) T lymphocytes in peripheral blood and an increase in the inflamed appendix. Reciprocal changes were observed in the CD45RA+ (naive) T lymphocyte subset. These changes were reflected in the local arterial and venous CD45RA and CD45RO T lymphocyte subsets. Proliferation studies showed an expanded functional repertoire of T lymphocytes in the inflamed appendix. Selective recruitment of memory T lymphocytes from the peripheral blood to the inflamed appendix was demonstrated.